A STUDY ON QUALITY TEACHING-LEARNING ENVIRONMENT ON SOCIAL AND EMOTIONAL DEVELOPMENT OF PRESCHOOLERS - SOUMYA HIRELINGANNAVAR,; MANJULA PATIL, (The Journal of Research ANGRAU, 2025)
A research study examining the quality of teaching and learning environments and their effects on the social and emotional growth of preschool children was carried out in Dharwad taluk, Karnataka, from 2018 to 2020. The research included a sample of 208 children, aged between 3 and 6 years, who were enrolled in various Early Childhood Care and Education (ECCE) centers located in both rural and urban regions of Dharwad taluk. The results conferred that children in centers characterized by medium-quality teaching-learning environments achieved significantly higher scores, averaging 36.13 ± 4.14, in social and emotional development compared to their peers in low-quality centers, regardless of whether they were in rural or urban areas. Notable differences were observed in specific areas, including emotional expression (5.23 ± 0.87), emotional adaptability (5.19 ± 0.97), emotion regulation arousal states (5.15 ± 0.99), behavioral regulation (5.19 ± 0.86), sense of self (4.90 ± 0.77), emotional themes in play (5.00 ± 0.65), and social interaction (5.46 ± 0.93), all of which were influenced by the quality of the teaching-learning environment in both settings.